Eastern Europe and the Commonwealth of indipendent states 1992 (London : Europa publications, 1992)
A reference aid for all those with business or professional interests in East European and Soviet affairs charting economic, political and cultural developments in Eastern Europe and the CIS.
Includes index.
Amirul
Keywords: independent states. -- eastern europe